ANALISIS PENGARUH ADOPSI XBRL TERHADAP ASIMETRI INFORMASI DENGAN CORPORATE GOVERNANCE SEBAGAI PEMODERASI (ANALYSIS OF XBRL ADOPTION’S IMPACT ON INFORMATION ASYMMETRY, WITH CORPORATE GOVERNANCE AS MODERATING VARIABLE) - Mahardika, Surya Aditama; Harahap, Siti Nurwahyuningsih (UI Scholars Hub, 2018)
This study investigates the impact of Extensible Business Reporting Language (XBRL) adoption on Information Asymmetry, with Corporate Governance (CG) as moderating variable. XBRL is a technology for financial reporting, to facilitate presentation of financial reports in standard format and enable greater accessibility for financial information for further analysis. Adoption of XBRL is expected to increase the quality of financial report and thus reduce information asymmetry. Impact of XBRL on the quality of financial report is strengthen by CG that in various previous studies is identified as a factor that improves quality of financial report. Samples under this study are listed firms in capital market in several Asia countries, i.e. Japan, South Korea, and Singapore. This study concludes that XBRL adoption results in information asymmetry decrease. CG has both direct impact and moderating effect on the relationship between XBRL and information asymmetry. CG strengthen the negative impact of XBRL on information asymmetry.